Analysis of Just-in-Time Inventory Management in Retail Companies to Reduce Operational Costs - Yosranindi, Ferdi (Generasi Sains Indonesia, 2024)
The current research paper examines the implementation of the Just-in-Time (JIT) management of inventory in the retail business enterprise and its practical use in cost reduction. The researcher identified ten retail companies, five using JIT systems and five using conventional inventory techniques; this was done through a descriptive design where surveys and structured interviews were administered. The main data sources include financial statements, inventory ledgers, and views of operation as well as supply-chain managers. The results show that the costs of holding inventory experienced a statistically significant decrease by entities that use JIT with an average reduction of about 300,000 a year, and the overall operations costs by about an average of half a million dollars. Moreover, JIT adopters were able to achieve higher stock turnover levels and less inventory out-of-stock situations, hence attaining a higher level of inventory efficiency. However, the JIT strategy is fraught with other problems including issues of coordination with the suppliers as well as the investment in the supporting technologies. The study, therefore, focuses on the strategic potential of JIT as a way of enhancing operational performance within the retail sector as well as outlining contextual limitations that has to be overcome so as to achieve lasting success.